2023
DOI: 10.1371/journal.pone.0281689
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins response of COVID-19 patients, COVID-19 vaccine recipients, and random individuals

Abstract: Background The development of specific immunoglobulins to COVID-19 after natural infection or vaccination has been proposed. The efficacy and dynamics of this response are not clear yet. Aim This study aims to analyze the immunoglobulins response among COVID-19 patients, COVID-19 vaccine recipients and random individuals. Methods A total of 665 participants including 233 COVID-19 patients, 288 COVID-19 vaccine recipients, and 144 random individuals were investigated for anti-COVID-19 immunoglobulins (IgA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The study found that the peak response for COVID-19 patients was between 16 and 30 days for IgG, 15 to 22 days for IgM, and 0 to 60 days for IgA. The levels of these antibodies gradually decreased after peaking, but were still detectable up to 300 days, with the exception of IgM antibodies which disappeared between 61 and 90 days in all patients [ 58 ]. It has been described that IgA antibodies, present in the serum, saliva, and bronchoalveolar washings of patients, are more effective in neutralizing virus than IgG antibodies [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the peak response for COVID-19 patients was between 16 and 30 days for IgG, 15 to 22 days for IgM, and 0 to 60 days for IgA. The levels of these antibodies gradually decreased after peaking, but were still detectable up to 300 days, with the exception of IgM antibodies which disappeared between 61 and 90 days in all patients [ 58 ]. It has been described that IgA antibodies, present in the serum, saliva, and bronchoalveolar washings of patients, are more effective in neutralizing virus than IgG antibodies [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As SARS-CoV-2 infection initiates in the upper respiratory tract, we sought to evaluate whether differences in mucosal IgG responses between non-pregnant and pregnant people may account for differences in clinical severity. IgG was quantified rather than IgA because titers of IgG and seroconversion rates of IgG are higher in response to mRNA vaccines ( 17 , 19 22 ). Vaccinated individuals had greater anti-S IgG titers than unvaccinated individuals, regardless of pregnancy status ( P < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in patients with low antigen exposure and mild symptoms, mucosal IgA may be detected in only about 15-20% of the cases [ 18 ], whereas serum IgA is usually absent. In addition, it is worth mentioning that vaccination, especially with mRNA vaccines, generally induces the expression of SARS-CoV-2 IgA antibodies [ 19 ], but their levels decrease quickly, whereas higher levels are observed in infected individuals [ 20 ]. In our case, the PCR tests acquired one day before and three weeks after the acute neurologic manifestation were negative.…”
Section: Discussionmentioning
confidence: 99%